Porous silver antibacterial coating material based on synchronous bimetal electroplating and single electrolytic deplating process and preparation method of porous silver antibacterial coating material

By applying porous silver antibacterial coating materials on bone implant devices, using bimetallic electroplating and electrolytic deplating processes to build porous structures, and introducing bone-promoting drugs, the shortcomings of bone implant devices in anti-infection and bone integration effects are solved, and the dual functions of coating materials in anti-infection and promoting bone integration are realized.

CN119506989APending Publication Date: 2025-02-25ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411301909.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing bone implantation devices have shortcomings in anti-infection and bone integration effects, and cannot meet the multiple complex needs of fracture and bone defect areas at the same time.

Method used

Using porous silver antibacterial coating materials based on synchronous bimetallic electroplating and single electrolytic deplating processes, silver-zinc composite antibacterial coating is introduced on the surface of titanium/stainless steel substrates through bimetallic electrochemical deposition process, and porous structures are constructed through electrolytic deplating process, and bone-promoting drugs are introduced in combination with ultrasonic impregnation loading process.

Benefits of technology

The dual functions of coating materials in anti-infection and promoting bone integration are realized, and cell adhesion and bone drug release are promoted through porous structures, drug release cycle is extended, and bone repair effect is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506989A_ABST
    Figure CN119506989A_ABST
Patent Text Reader

Abstract

The invention discloses a porous silver antibacterial coating material based on synchronous bimetal electroplating and single electrolytic deplating processes and a preparation method of the porous silver antibacterial coating material. The specific preparation process comprises the following steps: 1) removing impurities on the surface of the titanium / stainless steel substrate by using an environment-friendly cleaning agent and deionized water under an ultrasonic cleaning condition, and carrying out chemical film removal on the titanium / stainless steel substrate; (2) designing an Ag < + > / Zn < 2 + > composite electrolyte formula, and introducing a silver-zinc composite antibacterial coating on the surface of the titanium substrate by combining with a bimetallic electrochemical deposition process; (3) a stripping solution based on organic acid is designed, elemental zinc in the silver-zinc composite antibacterial coating is removed in combination with an electrolysis process, and a porous structure is controllably constructed in the coating; and (4) putting the sample into a solution of osteogenic factors, and carrying out ultrasonic impregnation, low-temperature nitrogen drying, dark vacuum packaging and irradiation sterilization to obtain the required porous silver antibacterial coating material. The coating has an excellent anti-infection function, meanwhile, a pore structure constructed in the coating and loaded factors can induce cell ingrowth, and the coating has good osseointegration performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation technology of antibacterial and bone repair materials, and in particular to a porous silver antibacterial coating material based on a synchronous bimetallic electroplating and a single electrolytic stripping process and a preparation method thereof. Background Art

[0002] Fractures and bone defects are very common orthopedic diseases, mainly caused by traffic accidents, surgery, etc. Once fractures and bone defects occur, bone implants / interventional devices are generally required for treatment. However, the bone implants / interventional devices currently used basically have no biological activity and cannot effectively deal with problems such as bone infection and poor bone integration encountered during bone tissue regeneration and repair.

[0003] In response to the above problems, many researchers have conducted research and development work around coating technology, such as iodine coating, silver coating, antibiotic coating, etc. for the treatment of bone infection; magnesium coating, zinc coating, etc. for promoting bone integration. However, the above existing coatings often only have a single function and cannot simultaneously meet the multiple and complex needs of fractures and bone defect areas. Therefore, the development of dual-function coatings that promote bone formation and resist infection is imminent.

[0004] Based on this, the present invention proposes a porous silver antibacterial coating material and a preparation method thereof based on a synchronous bimetallic electroplating and a single electrolytic stripping process. The present invention simultaneously introduces a silver-zinc composite antibacterial coating on the surface of a titanium / stainless steel substrate by using a bimetallic electrochemical deposition process, and combines electrolytic stripping and ultrasonic loading processes to introduce a pore structure that induces cell adhesion and ingrowth, and loads osteogenic drugs in the pores, providing a new strategy for preventing bone infection and treating fractures / bone defects. Summary of the invention

[0005] The purpose of the present invention is to provide a porous silver antibacterial coating material and a preparation method thereof based on a synchronous bimetallic electroplating and a single electrolytic stripping process to address the problems of poor anti-infection and bone integration of traditional bone implant devices. The coating material has excellent anti-infection function, and the pore structure constructed in the coating and the factors loaded can induce cell growth, and has good bone integration performance.

[0006] The present invention is implemented by the following technical solutions, which are as follows:

[0007] A method for preparing a porous silver antibacterial coating material based on a synchronous bimetallic electroplating and a single electrolytic stripping process comprises the following steps:

[0008] 1) Use environmentally friendly cleaning agents and deionized water to remove impurities on the surface of titanium / stainless steel substrates under ultrasonic cleaning conditions and perform chemical film removal;

[0009] 2) Design Ag+ / Zn 2+ The composite electrochemical deposition solution formula combines the bimetallic electrochemical deposition process to introduce a silver-zinc composite antibacterial coating on the surface of the titanium / stainless steel substrate;

[0010] 3) designing a deplating solution based on an organic acid, combining the electrolytic deplating process to remove the elemental zinc in the silver-zinc composite antibacterial coating in the deplating tank and controllably constructing a porous structure in the coating to obtain a porous silver elemental coating;

[0011] 4) placing the porous silver single substance coating in a solution of osteogenic growth factor, and obtaining the porous silver antibacterial coating material after ultrasonic impregnation, nitrogen drying, light-proof vacuum packaging and irradiation sterilization.

[0012] Further, in step 1), during the ultrasonic cleaning process, the environmentally friendly cleaning agent is used for cleaning at least once, and deionized water is used for cleaning several times, and each cleaning time is 5-30 minutes; the environmentally friendly cleaning agent includes: sodium carbonate 2-5g / L, sodium metasilicate pentahydrate 3-5g / L, sodium dodecanoate 10-15g / L, nitrilotriacetic acid 3-5ml / L, NP-10 (99%) 2-10g / L, LAB (99%) 5-8g / L, and the rest is deionized water; the ultrasonic power is 60-80w, and the temperature is 50-60°C;

[0013] During the chemical film removal process, an acidic chemical film removal liquid is used for immersion at room temperature. The acidic chemical film removal liquid specifically includes: 20v / v% phosphoric acid and 1v / v% hydrofluoric acid, and the rest is deionized water.

[0014] Further, in step 2), the Ag + / Zn 2+ The composite electrochemical deposition solution includes: 20-30 g / L silver nitrate, 1-5 g / L zinc sulfate, 1-6 g / L malic acid, 5-15 g / L sodium hydroxide, 40-60 g / L imidazole, 0.5-2.7 g / L nonylphenol polyoxyethylene lauryl ether, 30-60 g / L amino acid, 2-6 g / L sodium bicarbonate, and the rest is deionized water, and the pH value of the solution is controlled to be 8-10;

[0015] In the bimetallic electrochemical deposition process, a bidirectional pulse power supply electrochemical deposition mode is adopted, the working temperature is 30-35°C, the forward pulse width is 1-4ms, the forward duty cycle is 10-20%, and the negative current density is 0.2-1.3A / dm 2 , the deposition time is 10-60min, and the anode is a silver plate with a purity of not less than 99.99%;

[0016] The antibacterial coating has a thickness of 10-100 microns.

[0017] Further, in step 3), the organic acid-based deplating solution comprises: 5-10% organic acid, 1-5 g / L imidazole, 0.5-1.5 g / L potassium sodium tartrate, 1-5 ml / L sulfuric acid (RA), and the rest is deionized water; wherein the organic acid is one or more of citric acid, malic acid, tartaric acid, and acetic acid;

[0018] In the electrolytic stripping process, a bidirectional pulse power supply electrochemical stripping mode is adopted, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 1-5ms, the forward duty cycle is 10-30%, and the forward current density is 0.5-1.2A / dm 2 The stripping temperature is 25-35℃, and the stripping time is 10-15min. After stripping, use ultrapure water for ultrasonic cleaning 3-5 times, each time for 1-15min, and then dry with nitrogen at 60-80℃ for 1-5h.

[0019] Furthermore, in step 3), the stripping tank body is made of polyethylene (PP), the cathode is made of 304 rust-free steel plate, a water pump device and a filter device are arranged in the stripping tank to filter the solution and circulate and stir, and a swing device is arranged to swing the sample to remove the local accumulation of surrounding ion concentration;

[0020] The filter device has a power of 30-45W and a solution circulation rate of 30L / min;

[0021] The swing device adopts a 360-degree rotation mode with a rotation speed of 20-40r / min.

[0022] Further, in step 4), the osteogenic growth factor solution is one or more of bone morphogenetic protein 2 (BMP-2), activated transforming growth factor β (TGF-β), insulin-like growth factor 1 (IGF1), osteogenic growth peptide (OGP), and vascular endothelial growth factor (VEGF), with a concentration of 30-200 ng / ml;

[0023] The ultrasonic immersion power is 150-200W, the time is 10-20min, and the temperature is 4-10°C;

[0024] The nitrogen drying temperature is 4-10° C., the gas flow rate is 2-5 m / s, and the drying time is 5-20 min.

[0025] A porous silver antibacterial coating material based on synchronous bimetallic electroplating and single electrolytic stripping process is obtained by using any of the above-mentioned preparation methods.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1) The present invention uses titanium / stainless steel, silver nitrate, zinc sulfate, osteogenic factors, etc. as raw materials, and uses a combination of processes such as bimetallic electrochemical deposition, electrolytic stripping, ultrasonic immersion loading, and low-temperature nitrogen drying to obtain a porous silver antibacterial coating material based on synchronous bimetallic electroplating and single electrolytic stripping process;

[0028] 2) The present invention uses a combination of bimetallic electrochemical deposition and electrolytic stripping to form a silver coating material with a porous structure on the surface of the titanium / stainless steel substrate. + / Zn 2+ The composite electrochemical deposition solution formula, combined with the bimetallic electrochemical deposition process, successfully obtained a silver / zinc composite bimetallic coating on the surface of the titanium / stainless steel substrate; at the same time, relying on the different redox activities of silver and zinc, the electrolytic stripping process was used to selectively remove the zinc element in the silver-zinc composite antibacterial coating, but the silver element was intact to obtain a silver element coating with a porous structure inside. The construction of the porous silver element coating is based on the synergistic cooperation between the above-mentioned combined processes, while retaining the antibacterial active components, introducing drug loading sites and subsequent inducible cell adhesion functions.

[0029] 3) The pore structure inside the silver coating of the present invention has the function of serving as a bone-promoting drug loading and cell adhesion site. After successfully using the bimetallic electrochemical deposition + electrolytic stripping combined process to introduce a silver single substance coating with a pore structure, the pore structure can be used as an important physical space site. Therefore, the applicant successfully introduced the bone-promoting drug into the pore structure by combining the ultrasonic immersion loading + low-temperature nitrogen drying process, and obtained a composite structure of a layer of porous silver single substance coating + two layers of bone-promoting drug layers, which solved the technical problems of conventional titanium / stainless steel substrates and the difficulty of secondary introduction of drug loading sites on the coating surface, and provided the possibility for bone implantation / interventional device modification / secondary modification. On the other hand, when the bone implantation / interventional device product containing the above-mentioned composite functional coating is used for the treatment of diseases such as fractures / bone defects, the pore structure on the surface of the silver coating will first serve as a site for inducing cell adhesion. Compared with the flat surface of ordinary titanium / stainless steel, the pore structure is more conducive to the adhesion of cell pseudopodia therein. Cell adhesion is an important prerequisite for subsequent cell proliferation, differentiation, and migration, and can greatly promote the bone integration / bone repair process. The above modification strategy of further introducing a pore structure into the silver single substance coating is designed by the present invention in combination with multiple modification requirements of the bone implant device.

[0030] 4) The antibacterial coating material in the present invention has the functions of promoting cell adhesion, promoting osteogenesis, and resisting infection. When it is applied to the process of bone integration / bone repair, first, the cells can adhere the pseudopodia to the surface of the coating through the porous structure of the coating surface, completing the first step of bone repair; at the same time, the internal osteogenic drugs will dissolve and ooze out with the entry of tissue fluid, promoting the osteogenic differentiation of the surrounding cells and the formation of new bones, and because the microporous structure surrounds and forms a physical barrier, the internal osteogenic drug release cycle is greatly extended, overcoming the toxicity of drug burst release and matching the longer cycle of bone repair; and silver is an effective antibacterial active ingredient. In this process, the silver single substance coating will effectively prevent and treat the occurrence of bone infection by slowly dissolving silver ions, achieving the purpose of anti-infection. It is through the mutual cooperation and synergistic enhancement of the above-mentioned cell adhesion, osteogenesis, and anti-infection functions of the antibacterial coating material that fracture / bone repair can be efficiently treated, solving the clinical problems of high incidence of infection and poor bone integration / repair effect in the process.

[0031] 5) The coating preparation technology in the present invention is a platform technology, which can be modified on the surface of titanium / stainless steel substrates of any shape to meet the modification requirements of various bone implant / interventional device products. The process is convenient and universal, and provides a new strategy for the functional modification of bone implant / interventional device products. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the preparation process of the porous silver antibacterial coating material based on the synchronous bimetallic electroplating and single electrolytic stripping process of the present invention;

[0033] Figure 2 This is a silver ion release curve in the porous silver antibacterial coating material based on the simultaneous bimetallic electroplating and single electrolytic stripping process according to an embodiment of the present invention (A corresponds to Example 1, and B corresponds to Example 1). DETAILED DESCRIPTION

[0034] The present invention is further described below with reference to specific examples and accompanying drawings.

[0035] Comparative Example 1:

[0036] 1) Ultrasonic cleaning of TC4 samples: Clean once with environmentally friendly cleaning agent degreasing liquid (sodium carbonate 4g / L, sodium metasilicate pentahydrate 5g / L, sodium dodecanoate 12g / L, nitrilotriacetic acid 4ml / L, NP-10 (99%) 8g / L, LAB (99%) 6g / L, and the rest is deionized water), and clean three times with deionized water, each for 10 minutes, (the above cleaning is ultrasonic cleaning, the ultrasonic power is 70w, and the temperature is 55°C). After cleaning, the sample is soaked in acidic chemical defilming liquid (20v / v% phosphoric acid and hydrofluoric acid 1v / v%, and the rest is deionized water) at room temperature for 60s for chemical defilming, and then dried for use after deionized water cleaning.

[0037] 2) The above samples were immersed in Ag + Electrochemical deposition was carried out in an electrochemical deposition solution (formula: silver nitrate 25 g / L, malic acid 4 g / L, sodium hydroxide 10 g / L, imidazole 50 g / L, nonylphenol polyoxyethylene lauryl ether 1.2 g / L, amino acid 50 g / L, sodium bicarbonate 5 g / L, the rest is deionized water, solution pH value is 9.5) (working solution temperature 35 ° C, positive pulse width 3 ms, positive duty cycle 15%, negative current density 0.5 A / dm 2 , deposition time is 30min, the anode is 99.99% pure silver plate), and the obtained silver coating thickness is 20 microns.

[0038] 3) The sample was ultrasonically cleaned three times with ultrapure water (ultrasonic power 60 W, frequency 25 KHz, each cleaning time 10 min), and then dried, light-proof vacuum packed and irradiated for sterilization to obtain the silver antibacterial coating material.

[0039] The extract of the coating material was prepared and co-cultured with mesenchymal stem cells for 7 days. The CCK-8 test results showed that the cell survival rate was about 87.4%. The coating bonding strength was about 23.1 MPa using a universal testing machine. The antibacterial zone area of ​​the coating was about 2.68 cm 2 ; implanted into rat intramedullary infection model, bone infection disappeared after 4 weeks, and the bone integration effect of the sample surface was average, such as Figure 1 Figure B is the silver ion release curve of the porous silver antibacterial coating material based on the simultaneous bimetallic electroplating and single electrolytic stripping process in this example.

[0040] Embodiment 1:

[0041] 1) Ultrasonic cleaning of TC4 samples: Use environmentally friendly cleaning agent degreasing liquid (sodium carbonate 4g / L, sodium metasilicate pentahydrate 5g / L, sodium dodecanoate 12g / L, nitrilotriacetic acid 4ml / L, NP-10 (99%) 8g / L, LAB (99%) 6g / L, and the rest is deionized water) to clean once, and deionized water to clean three times, each time for 10 minutes, (the above cleaning is ultrasonic cleaning, the ultrasonic power is 70w, and the temperature is 55°C). After cleaning, use acidic chemical defilming liquid (20v / v% phosphoric acid and hydrofluoric acid 1v / v%, and the rest is deionized water) to soak the sample at room temperature for 60s for chemical defilming, and then dry it for use after deionized water cleaning.

[0042] 2) The above samples were immersed in Ag + / Zn 2+ The bimetallic electrochemical deposition was carried out in a composite electrochemical deposition solution (formula: silver nitrate 25 g / L, zinc sulfate 3 g / L, malic acid 4 g / L, sodium hydroxide 10 g / L, imidazole 50 g / L, nonylphenol polyoxyethylene lauryl ether 1.2 g / L, amino acid 50 g / L, sodium bicarbonate 5 g / L, the rest is deionized water, solution pH is 9.5) (working solution temperature 35 ° C, positive pulse width 3 ms, positive duty cycle 15%, negative current density 0.5 A / dm 2 , the anode is 99.99% pure silver plate, the deposition time is 30min), and the thickness of the obtained silver-zinc composite antibacterial coating is 25 microns.

[0043] 3) Place the silver-zinc composite antibacterial coating sample in a stripping tank (the tank body is made of PP material, the cathode is made of 304 stainless steel plate, a filter device is set in the electrolytic stripping tank to filter the solution and circulate and stir, and a swing device is set for the sample to swing to remove the local accumulation of surrounding ion concentration) for electrolytic stripping treatment, and a porous structure can be controllably constructed in the coating to obtain a porous silver single substance coating. Among them, the electrolytic stripping solution formula is: citric acid 100g / L, imidazole 4g / L, potassium sodium tartrate 1g / L, sulfuric acid (RA) 4ml / L, and the rest is deionized water; the stripping tank filter power is 30W, the solution circulation rate is 30L / min, the swing device adopts a 360-degree rotation mode, and the speed is 30r / min; a bidirectional pulse power supply electrochemical stripping mode is adopted, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 3ms, the forward duty cycle is 20%, and the forward current density is 0.7A / dm 2 The sample deplating temperature was 35°C and the deplating time was 10 min. After the deplating was completed, the sample was ultrasonically cleaned 3 times with ultrapure water, each cleaning time was 10 min, and then dried at 60°C for 2 h after nitrogen drying.

[0044] 4) placing the substrate with the porous silver single substance coating in a BMP-2 solution with a concentration of 100 ng / ml, ultrasonically impregnating (power of 180 W, time of 15 min, temperature of 4° C.), low-temperature nitrogen drying (4° C., gas flow rate of 4 m / s, drying time of 20 min), light-proof vacuum packaging and irradiation sterilization to obtain the porous silver antibacterial coating material.

[0045] Compared with Comparative Example 1, this embodiment introduces a porous structure into the silver coating by electroplating / stripping zinc, and at the same time introduces osteogenic growth factors into the porous structure. The extract of the above coating material is prepared and co-cultured with mesenchymal stem cells for 7 days. The CCK-8 test results show that the cell survival rate is about 90.8%; the coating bonding strength is about 28.5MPa when tested by a universal testing machine; the coating antibacterial zone area is about 3.13cm 2 ; It was implanted into a rat intramedullary infection model, and the bone infection disappeared after 4 weeks. The sample surface had excellent bone integration effect, such as Figure 1 A in the figure is the silver ion release curve of the porous silver antibacterial coating material based on the simultaneous bimetallic electroplating and single electrolytic stripping process in this example.

[0046] Embodiment 2:

[0047] 1) Ultrasonic cleaning of TC4 samples: Use environmentally friendly cleaning agent degreasing liquid (sodium carbonate 4g / L, sodium metasilicate pentahydrate 5g / L, sodium dodecanoate 12g / L, nitrilotriacetic acid 4ml / L, NP-10 (99%) 8g / L, LAB (99%) 6g / L, and the rest is deionized water) to clean once, and deionized water to clean three times, each time for 10 minutes, (the above cleaning is ultrasonic cleaning, the ultrasonic power is 70w, and the temperature is 55°C). After cleaning, use acidic chemical defilming liquid (20v / v% phosphoric acid and hydrofluoric acid 1v / v%, and the rest is deionized water) to soak the sample at room temperature for 60s for chemical defilming, and then dry it for use after deionized water cleaning.

[0048] 2) The above samples were immersed in Ag + / Zn 2+ The bimetallic electrochemical deposition was carried out in a composite electrochemical deposition solution (formula: silver nitrate 25 g / L, zinc sulfate 3 g / L, malic acid 4 g / L, sodium hydroxide 10 g / L, imidazole 50 g / L, nonylphenol polyoxyethylene lauryl ether 1.2 g / L, amino acid 50 g / L, sodium bicarbonate 5 g / L, the rest is deionized water, solution pH is 9.5) (working solution temperature 35 ° C, positive pulse width 3 ms, positive duty cycle 15%, negative current density 0.5 A / dm 2 , the anode is 99.99% pure silver plate, the deposition time is 30min), and the thickness of the obtained silver-zinc composite antibacterial coating is 25 microns.

[0049] 3) Place the silver-zinc composite antibacterial coating sample in a stripping tank (the tank body is made of PP material, the cathode is made of 304 stainless steel plate, a filter device is set in the electrolytic stripping tank to filter the solution and circulate and stir, and a swing device is set for the sample to swing to remove the local accumulation of surrounding ion concentration) for electrolytic stripping treatment, and a porous structure can be controllably constructed in the coating to obtain a porous silver single substance coating. Among them, the electrolytic stripping solution formula is: citric acid 100g / L, imidazole 4g / L, potassium sodium tartrate 1g / L, sulfuric acid (RA) 4ml / L, and the rest is deionized water; the stripping tank filter power is 30W, the solution circulation rate is 30L / min, the swing device adopts a 360-degree rotation mode, and the speed is 30r / min; a bidirectional pulse power supply electrochemical stripping mode is adopted, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 3ms, the forward duty cycle is 20%, and the forward current density is 0.7A / dm 2 The sample deplating temperature is 35°C, and the deplating time is 10 min. After the deplating is completed, the sample is ultrasonically cleaned 3 times with ultrapure water, each cleaning time is 10 min, and then nitrogen dried and further dried at 60°C for 2 h. After light-proof vacuum packaging and irradiation sterilization, the porous silver antibacterial coating material is obtained.

[0050] Compared with Example 1, this example reduces the load of BMP-2 in the porous structure. The extract of the coating material was prepared and co-cultured with mesenchymal stem cells for 7 days. The CCK-8 test results showed that the cell survival rate was about 86.2%; the coating bonding strength was about 27.9 MPa using a universal testing machine; the coating inhibition zone area was about 3.36 cm 2 ; It was implanted into a rat intramedullary infection model. The bone infection disappeared after 4 weeks, and the bone integration effect of the sample surface was average.

[0051] Embodiment 3:

[0052] 1) Ultrasonic cleaning of TC4 samples: Use environmentally friendly cleaning agent degreasing liquid (sodium carbonate 4g / L, sodium metasilicate pentahydrate 5g / L, sodium dodecanoate 12g / L, nitrilotriacetic acid 4ml / L, NP-10 (99%) 8g / L, LAB (99%) 6g / L, and the rest is deionized water) to clean once, and deionized water to clean three times, each time for 10 minutes, (the above cleaning is ultrasonic cleaning, the ultrasonic power is 70w, and the temperature is 55°C). After cleaning, use acidic chemical defilming liquid (20v / v% phosphoric acid and hydrofluoric acid 1v / v%, and the rest is deionized water) to soak the sample at room temperature for 60s for chemical defilming, and then dry it for use after deionized water cleaning.

[0053] 2) The above samples were immersed in Ag + / Zn 2+The bimetallic electrochemical deposition was carried out in a composite electrochemical deposition solution (formula: silver nitrate 20 g / L, zinc sulfate 5 g / L, malic acid 4 g / L, sodium hydroxide 10 g / L, imidazole 50 g / L, nonylphenol polyoxyethylene lauryl ether 1.2 g / L, amino acid 50 g / L, sodium bicarbonate 5 g / L, the rest is deionized water, solution pH is 9.5) (working solution temperature 35 ° C, forward pulse width 3 ms, forward duty cycle 15%, negative current density 0.5 A / dm 2 , the anode is 99.99% pure silver plate, the deposition time is 60min), and the thickness of the obtained silver-zinc composite antibacterial coating is 30 microns.

[0054] 3) Place the silver-zinc composite antibacterial coating sample in a stripping tank (the tank body is made of PP material, the cathode is made of 304 stainless steel plate, a filter device is set in the electrolytic stripping tank to filter the solution and circulate and stir, and a swing device is set for the sample to swing to remove the local accumulation of surrounding ion concentration) for electrolytic stripping treatment, and a porous structure can be controllably constructed in the coating to obtain a porous silver single substance coating. Among them, the electrolytic stripping solution formula is: citric acid 100g / L, imidazole 4g / L, potassium sodium tartrate 1g / L, sulfuric acid (RA) 4ml / L, and the rest is deionized water; the stripping tank filter power is 30W, the solution circulation rate is 30L / min, the swing device adopts a 360-degree rotation mode, and the speed is 30r / min; a bidirectional pulse power supply electrochemical stripping mode is adopted, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 3ms, the forward duty cycle is 20%, and the forward current density is 0.7A / dm 2 The sample deplating temperature was 35°C and the deplating time was 10 min. After the deplating was completed, the sample was ultrasonically cleaned 3 times with ultrapure water, each cleaning time was 10 min, and then dried at 60°C for 2 h after nitrogen drying.

[0055] 4) The above sample was placed in a BMP-2 solution with a concentration of 100 ng / ml, ultrasonically impregnated (power of 180 W, time of 15 min, temperature of 4°C), low-temperature nitrogen dried (4°C, gas flow rate of 4 m / s, drying time of 20 min), light-proof vacuum packaging and irradiation sterilization to obtain a porous silver antibacterial coating material.

[0056] Compared with Example 1, this embodiment reduces the Ag + / Zn 2+ The extract of the coating material was prepared and co-cultured with mesenchymal stem cells for 7 days. The CCK-8 test results showed that the cell survival rate was about 88.7%; the coating bonding strength was about 24.2MPa using a universal testing machine; the coating inhibition zone area was about 3.51cm 2; It was implanted into a rat intramedullary infection model. After 4 weeks, the bone infection disappeared. The pore structure on the sample surface became larger, and the bone integration effect was improved compared with Example 1.

Claims

1. A method for preparing a porous silver antibacterial coating material based on a synchronous bimetallic electroplating and a single electrolytic stripping process, characterized in that: The following steps are involved: 1) Use environmentally friendly cleaning agents and deionized water to remove impurities on the surface of titanium / stainless steel substrates under ultrasonic cleaning conditions and perform chemical film removal; 2) Design Ag + / Zn 2+ The composite electrochemical deposition solution formula combines the bimetallic electrochemical deposition process to introduce a silver-zinc composite antibacterial coating on the surface of the titanium / stainless steel substrate; 3) designing a deplating solution based on an organic acid, combining the electrolytic deplating process to remove the elemental zinc in the silver-zinc composite antibacterial coating in the deplating tank and controllably constructing a porous structure in the coating to obtain a porous silver elemental coating; 4) placing the porous silver single substance coating in a solution of osteogenic growth factor, and obtaining the porous silver antibacterial coating material after ultrasonic impregnation, nitrogen drying, light-proof vacuum packaging and irradiation sterilization.

2. The method for preparing a porous silver antibacterial coating material based on simultaneous bimetallic electroplating and single electrolytic stripping process according to claim 1, characterized in that: In step 1), during the ultrasonic cleaning process, the environmentally friendly cleaning agent is used for cleaning at least once, and deionized water is used for cleaning several times, and each cleaning time is 5-30 minutes; the environmentally friendly cleaning agent includes: sodium carbonate 2-5g / L, sodium metasilicate pentahydrate 3-5g / L, sodium dodecanoate 10-15g / L, nitrilotriacetic acid 3-5ml / L, NP-10 (99%) 2-10g / L, LAB (99%) 5-8g / L, and the rest is deionized water; the ultrasonic power is 60-80w, and the temperature is 50-60°C; During the chemical film removal process, an acidic chemical film removal liquid is used for immersion at room temperature. The acidic chemical film removal liquid specifically includes: 20v / v% phosphoric acid and 1v / v% hydrofluoric acid, and the rest is deionized water.

3. The method for preparing a porous silver antibacterial coating material based on simultaneous bimetallic electroplating and single electrolytic stripping process according to claim 1, characterized in that: In step 2), the Ag + / Zn 2+ The composite electrochemical deposition solution includes: 20-30 g / L silver nitrate, 1-5 g / L zinc sulfate, 1-6 g / L malic acid, 5-15 g / L sodium hydroxide, 40-60 g / L imidazole, 0.5-2.7 g / L nonylphenol polyoxyethylene lauryl ether, 30-60 g / L amino acid, 2-6 g / L sodium bicarbonate, and the rest is deionized water, and the pH value of the solution is controlled to be 8-10; In the bimetallic electrochemical deposition process, a bidirectional pulse power supply electrochemical deposition mode is adopted, the working temperature is 30-35°C, the forward pulse width is 1-4ms, the forward duty cycle is 10-20%, and the negative current density is 0.2-1.3A / dm 2 , the deposition time is 10-60min, and the anode is a silver plate with a purity of not less than 99.99%; The antibacterial coating has a thickness of 10-100 microns.

4. The method for preparing a porous silver antibacterial coating material based on simultaneous bimetallic electroplating and single electrolytic stripping process according to claim 1, characterized in that: In step 3), the organic acid-based deplating solution comprises: 5-10% organic acid, 1-5 g / L imidazole, 0.5-1.5 g / L potassium sodium tartrate, 1-5 ml / L sulfuric acid (RA), and the rest is deionized water; wherein the organic acid is one or more of citric acid, malic acid, tartaric acid, and acetic acid; In the electrolytic stripping process, a bidirectional pulse power supply electrochemical stripping mode is adopted, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 1-5ms, the forward duty cycle is 10-30%, and the forward current density is 0.5-1.2A / dm 2 The stripping temperature is 25-35℃, and the stripping time is 10-15min. After stripping, use ultrapure water for ultrasonic cleaning 3-5 times, each time for 1-15min, and then dry with nitrogen at 60-80℃ for 1-5h.

5. The method for preparing a porous silver antibacterial coating material based on simultaneous bimetallic electroplating and single electrolytic stripping process according to claim 1, characterized in that: In step 3), the stripping tank body is made of polyethylene (PP), the cathode is made of 304 rust-free steel plate, a water pump device and a filter device are arranged in the stripping tank to filter the solution and circulate and stir, and a swing device is arranged to swing the sample to remove the local accumulation of surrounding ion concentration; The filter device has a power of 30-45W and a solution circulation rate of 30L / min; The swing device adopts a 360-degree rotation mode with a rotation speed of 20-40r / min.

6. The method for preparing a porous silver antibacterial coating material based on simultaneous bimetallic electroplating and single electrolytic stripping process according to claim 1, characterized in that: In step 4), the osteogenic growth factor solution is one or more of bone morphogenetic protein 2 (BMP-2), activated transforming growth factor β (TGF-β), insulin-like growth factor 1 (IGF1), osteogenic growth peptide (OGP), and vascular endothelial growth factor (VEGF), with a concentration of 30-200 ng / ml; The ultrasonic immersion power is 150-200W, the time is 10-20min, and the temperature is 4-10°C; The nitrogen drying temperature is 4-10° C., the gas flow rate is 2-5 m / s, and the drying time is 5-20 min.

7. A porous silver antibacterial coating material based on simultaneous bimetallic electroplating and single electrolytic stripping process, characterized in that: The method is adopted as claimed in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Double-pulse plating silver solution and technique thereof

    CN101629313A

  • Bidirectional pulse silver-plating method

    CN103436931A

  • Porous biological ceramic coating with antibiosis and bone promoting functions as well as preparation method and application thereof

    CN110565144A